Teologie kroniek/Theology Chronicle: The Politics of Salvation: Values, Ideology and the South African National Curriculum - J Jansen (Verbum et Ecclesia, 2004)
The South African experience offers dramatic examples of how the curriculum remains a lightning rod for the values contestation in divided societies. Despite its overwhelming election mandate, the ruling party found that changing the curriculum required the consent of powerful and less powerful sections of society - whose opposition extended across racial lines. This essay reports on research into attempts by the post- apartheid state to introduce values explicitly into the school curriculum, and how communities - mobilised primarily on the common front of religious values - combined to decelerate if not reverse radical curriculum reforms. The most important finding from this work is that underestimating the power of faith-based communities is likely to undermine curriculum reforms that touch on matters of values, conscience and religious commitment.